Transcriptional regulator PRDM12 is essential for human pain perception - Chen, Ya-Chun; Auer-Grumbach, Michaela; Matsukawa, Shinya; Zitzelsberger, Manuela; Themistocleous, Andreas C.; Strom, Tim M.; Samara, Chrysanthi; Moore, Adrian W.; Cho, Lily Ting-Yin; Young, Gareth T.; Weiss, Caecilia; Schabhüttl, Maria; et al. (Nature genetics, 2015)
Geoffrey Woods, Jan Senderek and colleagues show that biallelic mutations in PRDM12 cause congenital insensitivity to pain. They further show that PRDM12 is expressed in nociceptors and their progenitors and participates in sensory neuron development in Xenopus.